The importance of scale in comparative microbiome research: New insights from the gut and glands of captive and wild lemurs. Issue 10 (1st April 2019) - Greene, Lydia K.; Bornbusch, Sally L.; McKenney, Erin A.; Harris, Rachel L.; Gorvetzian, Sarah R.; Yoder, Anne D.; Drea, Christine M.
Abstract: Research on animal microbiomes is increasingly aimed at determining the evolutionary and ecological factors that govern host–microbiome dynamics, which are invariably intertwined and potentially synergistic. We present three empirical studies related to this topic, each of which relies on the diversity of Malagasy lemurs (representing a total of 19 species) and the comparative approach applied across scales of analysis. In Study 1, we compare gut microbial membership across 14 species in the wild to test the relative importance of host phylogeny and feeding strategy in mediating microbiome structure. Whereas host phylogeny strongly predicted community composition, the same feeding strategies shared by distant relatives did not produce convergent microbial consortia, but rather shaped microbiomes in host lineage‐specific ways, particularly in folivores. In Study 2, we compare 14 species of wild and captive folivores, frugivores, and omnivores, to highlight the importance of captive populations for advancing gut microbiome research. We show that the perturbational effect of captivity is mediated by host feeding strategy and can be mitigated, in part, by modified animal management. In Study 3, we examine various scent‐gland microbiomes across three species in the wild or captivity and show them to vary by host species, sex, body site, and a proxy of social status. These rare data provide support for the bacterial fermentation hypothesis in olfactory signal production and implicate steroid hormones as mediators of microbial community structure. We conclude by discussing the role of scale in comparative microbial studies, the links between feeding strategy and host–microbiome coadaptation, the underappreciated benefits of captive populations for advancing conservation research, and the need to consider the entirety of an animal's microbiota. Ultimately, these studies will help move the field from exploratory to hypothesis‐driven research. Abstract : The phylogenetic and ecological diversity of lemurs makes them useful subjects for comparative microbiome research across scales of analysis.